Empowering High School Teachers with Computer Systems and Networking through Skills-Training in the Case of Supang National High School, Philippines - Ymalay, Lea P.; Martires, Rodney M.; Cainday III, Simeon J.; Alminaza, Reiner Jun G. (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
This study explored the effectives of conducting a computer training designed to improve the skills of teachers in the field of ICT specifically in Computer Systems Servicing. The challenge of limited access to skills training for teachers in ICT subject motivated the researchers to conduct a Community Extension Service to Supang National High School that covers the topic on Computer Services and Network for 8 hours proficiency training. A Significant Improvement in the participants’ knowledge and skills revealed after the Pre and Post Training assessments. Initially, 36 of the 54 participants demonstrated no prior knowledge or skills in CSS and after the training, none of the participants remain at this initial level, with all achieving higher scores on the post-training assessment especially 29 of the 54 participants have acquired a lot of knowledge and skills. This training demonstrates the effectiveness of targeted professional development in addressing the skills gap among ICT teachers and has the potential to improve the quality of CSS instruction and enhance student learning outcomes.